Developing a thematic-integrative instructional kit based on PBL model for fourth graders - Arnoldus Helmon (Jurnal Prima Edukasia, 2017)
This study aims at producing a suitable and effective thematic-integrative instructional kit based on the PBL model to improve the critical thinking ability and care-for-environment character of the fourth graders of SDN Serayu. It used the RD design of Borg and Gall. The subjects were teachers and students of grade four of SDN Serayu, Yogyakarta City. The data were obtained through interviews, a questionnaire, observation, and a test. The product effectiveness was tested by using a quasi-experiment. The data were analyzed qualitatively and quantitatively through t-test at 95% confidence interval. The results showed that the product is suitable for use, which is evidenced by the mean score of syllabi at 44.5, lesson plan at 74, the instructional textbook at 56.5, students worksheet at 33.5, and the assessment instrument at 21, all of which are in a very good category. The product could improve the students’ critical thinking ability which is evidenced by the significance value standing at 0.000 for t-test of two experimental groups (IVA and IVC) with the control group  (IVB). The product was effective in improving the care-for-environment character of students which is evidenced by the significance value standing at 0.000 for t-test of two experimental groups with the control group.